A review of the Palearctic Ptycerata Ely, 1910 (= Caulastrocecis Chrétien, 1931, syn. nov.) based on morphology (Lepidoptera, Gelechiidae) - Bidzilya, Oleksiy; Karsholt, Ole (Zootaxa, 2021)
The genus Ptycerata Ely, 1910 is recognised as a senior synonym of Caulastrocecis Chrétien, 1931, syn. nov., and revised in the Palearctic region. Nine species are recognised as valid. Three new species are described: Ptycerata sumpichi sp. nov. (Italy), Ptycerata nupponeni sp. nov. (Russia: Altai) and Ptycerata transbaikalica sp. nov. (Russia: Zabaikalskiy kray). Three new synonyms are established: Aristotelia salinatrix Meyrick, 1926, syn. nov. of Ptycerata furfurella (Staudinger, 1871) comb. nov., Xystophora tripunctella Snellen, 1884 syn. nov. of Ptycerata pudicella (Mann, 1861) comb. nov.; Aristotelia condensata Meyrick, 1928 syn. nov. of Ptycerata interstratella (Christoph, 1872) comb. nov. Further new generic combinations are proposed: Ptycerata gypsella (Constant, 1893) comb. nov., Ptycerata cryptoxena (Gozmány, 1952) comb. nov., Ptycerata perexigella (Junnilainen, 2010) comb. nov. In order to stabilise nomenclature lectotypes are designated for Ptycerata busckella Ely, 1910, Gelechia furfurella Staudinger, 1871, Hypsolophus pudicellus Mann, 1861, Aristotelia condensata Meyrick, 1928 and Aristotelia interstratella Christoph, 1872. The female genitalia of P. interstratella are described for the first time. Ptycerata pudicella is recorded as new for Cyprus and Mongolia, and P. interstratella as new from Kazakhstan, Kyrgyzstan, Tadzhikistan and Iran. Ptycerata pudicellus is removed from the list of Lepidoptera found in Spain.